(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Virtual (VR) and Augmented reality (AR) represent excellent tools for surgeons to understand spatial relationships, to train their workflow to improve surgery results. By providing realistic haptic feedback, implementing 3D-printed organ phantoms to those tools, their benefit gets even more compelling, increasing their immersion. In this work investigates the realism of organ phantoms regarding physical hardness, touch and feel. In a user study with 12 surgeons, we evaluated casted liver phantoms in 50 %, scale of the actual liver size. Results from surgeons allowed the configuration of a measurement tool for exact exploration of realistic haptics within this context.